Clinical neuroimmunology multiple sclerosis and related disorders - Rizvi, Syed A.; Coyle, Patricia K.; SpringerLink (Online service). (New York Humana Press, 2011)
Introduction to basic neuroimmunology and principles of immunotherapy and also serves as a thorough guide to immune-mediated disorders of the central and peripheral nervous system, as well as other systemic disorders with a significant neuroimmunologic component. The chapters are written by experts in their fields and include the most up to date scientific information. This volume is made to simplify complex immunological mechanisms and to focus on practical patient-related issues. Clinical Neuroimmunology: Multiple Sclerosis and Related Disorders is an invaluable addition to the literature and will be of significant interest to neurologists, residents and fellows, internists, and general practitioners who treat patients with neurologic disorders and other systemic autoimmune diseases.
MS: Pathology and Immunology -- MS: Epidemiology and Genetics -- MS: Clinical Features, Symptom Management, and Diagnosis -- Advances in Magnetic Resonance Imaging of Multiple Sclerosis -- Disease Modifying Agents in the Treatment of Multiple Sclerosis -- Pediatric Multiple Sclerosis -- Is Multiple Sclerosis a Vascular Disease? -- Multiple Sclerosis: The Next 20 Years -- Introduction to Neuroimmunology -- Acute Disseminated Encephalomyelitis -- Neuromyelitis Optica Spectrum Disorders -- The Neuroimmunology of Cancer -- Infections of the Central Nervous System -- The Neuroimmunology of Cortical Disease (Dementia, Epilepsy, and Autoimmune Encephalopathies) -- Autoimmune Movement Disorders -- CNS Vasculitis -- Principles of Immunotherapy -- Immunologic Disorders of Neuromuscular Junction and Muscle -- Autoimmune Neuropathies -- Systemic Autoimmune Diseases with Neurological Manifestations.
Electronic reproduction.
Keywords: Neuroimmunology; Electronic books